Photodegradation of 2-chlorophenol over ZnO/KCC-1: Reaction optimization by response surface methodology - Ros Shazuin Rayyanu, Mohd Zaki; Lim, X. R.; Herma Dina, Setiabudi; Nur Fitriah, Mohd Jaafar (Elsevier Ltd, 2023)
Removing 2-chlorophenol (2CP) from water is an imperative task due to its toxicity. Various methods have been introduced for 2CP removal, and photocatalytic degradation is one of the best alternative solutions due to its effectiveness and simple process. This study focused on the potency of ZnO/KCC-1 as an effective photocatalyst for 2CP elimination from aqueous solutions. ZnO/KCC-1 was prepared by impregnation of commercial ZnO precursor into the synthesized KCC-1. The synthesized Zn/KCC-1 was characterized by using TEM, FESEM, XRD, FTIR, and PL. The characterization results revealed that the addition of ZnO did not cause the collapse of the dendrimeric structure of KCC-1. The analysis via response surface methodology (RSM) over independent variables of initial concentration (X1), catalyst dosage (X2), and pH (X3) revealed that X2 was the most essential variable, while X1 was the least significant variable. The ideal parameter for 2CP degradation was achieved at X1 = 10 mg/L, X2 = 2 g/L, and X3 = 10 with photodegradation efficiency (Y) of 90.62% (predicted) and 88.93% (experimental). This research revealed that ZnO/KCC-1 had a good potential for photocatalytic degradation of 2CP from an aqueous solution.